Swimming Performance and Oxygen Consumption as Non-lethal Indicators of Production Traits in Atlantic Salmon and Gilthead Seabream - Palstra, Arjan P.; Kals, Jeroen; Böhm, Thijs; Bastiaansen, John W. M.; Komen, Hans (Frontiers in Physiology, 2020)
The aim of this study was to investigate swimming performance and oxygen consumption as non‐lethal indicator traits of production parameters in Atlantic salmon Salmo salar L. and Gilthead seabream Sparus aurata L. A total of 34 individual fish of each species were subjected to a series of experiments: 1) a critical swimming speed (Ucrit) test in a swim-gutter, followed by 2) two starvation-refeeding periods of 42 days, and 3) swimming performance experiments coupled to respirometry in swim-tunnels. Ucrit was assessed first to test it as a predictor trait. Starvation-refeeding traits included body weight; feed conversion ratio based on dry matter; residual feed intake; average daily weight gain and loss. Swim-tunnel respirometry provided oxygen consumption in rest and while swimming at the different speeds, optimal swim speed and minimal cost of transport. After experiments, fish were dissected and measured for tissue weights and body composition in terms of dry matter, ash, fat, protein and moist, and energy content. The Ucrit test design was able to provide individual Ucrit values in high throughput manner. The residual Ucrit (RUcrit) should be considered in order to remove the size dependency of swimming performance. Most importantly, RUcrit predicted fillet yield in both species. The minimal cost of transport, the oxygen consumption when swimming at Uopt, added predictive value to the seabream model for feed intake.